Differential relationships between cannabis consumption and sleep health as a function of HIV status. (1st November 2018) - Lim, Aaron C.; Thames, April D.
Highlights: HIV moderates the relationship between sleep quality and cannabis consumption. Sleep quality is negatively associated with cannabis consumption in HIV- controls. Sleep quality is not associated with cannabis consumption in HIV + individuals. Abstract: Background: There is evidence that regular cannabis use has negative effects on sleep health. Relative to HIV- populations, HIV + individuals consistently report greater sleep impairments. The number of HIV + individuals reporting frequent cannabis use, often to treat sleep issues, has significantly increased recently. It is unknown, however, if HIV status moderates the association between cannabis use and sleep health. The current study, therefore, examines these associations in a sample of HIV + and HIV- adults. Methods: HIV + and HIV- (N = 107) individuals completed one laboratory visit. Participants completed a 30-day drug use history questionnaire quantifying consumption of cannabis, cigarettes, and alcohol, and a sleep health questionnaire. To verify substance use and HIV status, participants completed a urine toxicology screening and serology testing. Results: HIV + individuals demonstrated lower sleep health than HIV- individuals. Linear regressions indicated that HIV status moderated the association between total 30-day cannabis consumption and sleep health; cannabis consumption was negatively associated with sleep health in HIV-, but not HIV + individuals. This interactive effect was significant after examining cigarette/alcohol use, depression symptoms, and demographic variables as covariates. Conclusions: These results corroborate studies demonstrating an inverse relationship between sleep health and cannabis consumption. This study also suggests that factors other than cannabis may be associated with lower sleep health in HIV + individuals. Emerging studies suggest that inflammation may mediate effects of cannabis on HIV infection. Future studies examining this mechanism are warranted to understand cannabis further and sleep in HIV + individuals.